2003
DOI: 10.1097/00007632-200301150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Donor Site Morbidity After Anterior Iliac Crest Bone Harvest for Single-Level Anterior Cervical Discectomy and Fusion

Abstract: A large percentage of patients report chronic donor site pain after anterior ICBG donation, even when only a single-level ACDF procedure is performed. Moreover, long-term functional impairment can also be significant. Patients should be counseled regarding these potential problems, and alternative sources of graft material should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
498
3
18

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 802 publications
(528 citation statements)
references
References 18 publications
9
498
3
18
Order By: Relevance
“…of the donor site in 10% of cases and major complications in 5.8% of cases, requiring therapeutic modifications, surgical revision, and prolongation of the duration of hospitalization. Silber et al [22] observed that 26.1% of patients reported pain of the donor site, with visual analog scale values between 3.8 and 10 on a scale of 10. The use of vertebral cages responds to biomechanical imperatives and, by use of bone harvested in situ during the corpectomy, avoids complications involving the bone harvest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of the donor site in 10% of cases and major complications in 5.8% of cases, requiring therapeutic modifications, surgical revision, and prolongation of the duration of hospitalization. Silber et al [22] observed that 26.1% of patients reported pain of the donor site, with visual analog scale values between 3.8 and 10 on a scale of 10. The use of vertebral cages responds to biomechanical imperatives and, by use of bone harvested in situ during the corpectomy, avoids complications involving the bone harvest.…”
Section: Discussionmentioning
confidence: 99%
“…However, morbidity involving the site of graft harvest remains high and can compromise the often satisfactory clinical result of cervical nerve root and spinal cord decompression [3,22].…”
Section: Introductionmentioning
confidence: 99%
“…Silber et al [86] noticed serious impairments in functional activities of daily living in about 10% of patients due to the iliac crest site and mean VAS was 3.8 at 4 years follow-up. In contrast, Shamsaldin et al [84] demonstrated that after harvesting bone from the iliac crest for 1-level ACDF, 92% had no persisting pain after 1 year.…”
Section: Complicationsmentioning
confidence: 99%
“…Graft donor site pain and morbidity is a liberally used criticism of using autograft [86]. Silber et al [86] noticed serious impairments in functional activities of daily living in about 10% of patients due to the iliac crest site and mean VAS was 3.8 at 4 years follow-up.…”
Section: Complicationsmentioning
confidence: 99%
“…Although there is still controversy about the necessity of fusion after anterior cervical discectomy [25], most authors agree that fusion stabilizes the cervical spine and maintains the disc height, while decompressing the spinal cord and roots [1,30]. However, autogenous tricotical iliac bone, which is widely used in ACDF as interbody graft, is associated with donorsite morbidity as well as graft problems [23,27].…”
Section: Introductionmentioning
confidence: 99%